Macular Hole Progression following Ocriplasmin Intravitreal Injection. (14th December 2014) - Casswell, Edward; Fernandez-Sanz, Guillermo; Mitry, Danny; Luk, Sheila; Zakir, Rahila
Abstract : Ocriplasmin is a protease which has been approved for the treatment of symptomatic vitreomacular adhesion (VMA). A 63-year-old presented with blurred vision in the left eye and a best corrected visual acuity of 6/18. Optical coherence tomography revealed VMA with an underlying macular hole and she subsequently underwent a left intravitreal ocriplasmin injection. One week after the injection, VMA had been released but with enlargement of the macular hole and a drop in her BCVA to 6/60. This persisted at 1 month after the injection. It is important to warn patients that ocriplasmin may lead to an enlargement of their macular hole with resultant loss in visual acuity.